Situs Gua Pawon sebagai Sumber Belajar dalam Pembelajaran Sejarah Berbasis Ekopedagogi - M. Maman Sumaludin (Badan Riset dan Inovasi Nasional (BRIN), 2022)
The quality of education is one of the elements of the sustainable development goal. In the world of education, learning history plays a role in forming student’s character. This article aims to describe the implementation of ecopedagogy-based history learning by utilizing the Pawon Cave Site as a source of history learning. This qualitative research used a naturalistic inquiry method. The data was collected using interviews and observations techniques which then supplemented by documentation and field notes, also literature study. Data analysis consists of three steps, those are data reduction, data display, data verification and conclusions. This research was conducted on students of class X IPS at SMAN 4 Bandung, consisting of four classes in the even semester of the academic year of 2019/2020. Meanwhile, the historical excursions were conducted at the Pawon Cave Site in West Bandung Regency. Based on the results of the study, the Pawon Cave Site was a prehistoric human settlement (Pawon Man), who lived in harmony with the environment on the west side of the Bandung Prehistoric Lake. This historical source is a potential source of ecopedagogy-based historical learning. The Pawon Cave site as a learning resource in ecopedagogy based historical learning can develop ecological intelligence, application of green behaviour and historical awareness in students in order to create quality education in sustainable development.